Tax incentives as carrots for solar energy adoption (2023)
This study explores the influence of the fiscal incentives introduced by Law 1715 of 2014 on the stock of solar panels, an indicator for solar energy adoption in Colombia. The policy provides a series of incentives, including up to a 50% income tax deduction, VAT exclusions for goods and services related to Non-Conventional Renewable Energy Sources (NCRES) projects, tariff exemptions for NCRES project inputs, and an accelerated depreciation regime for machinery, equipment, and civil works used in NCRES projects. I use a synthetic control approach to construct a credible counterfactual, allowing for a precise evaluation of the policy's impact. Furthermore, I fortify my findings by utilizing Synthetic Difference-in-Differences estimators, which corroborate the results obtained from the synthetic control method. The findings suggest that Law 1715 has led to an increase in the stock of solar panels, exceeding the growth that would have been observed in the absence of the policy. This study underscores the potential effectiveness of fiscal incentives in promoting the adoption of renewable energy.